2007
DOI: 10.1097/01.prs.0000258403.49584.ec
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TGF-??2 Antibody Therapy Inhibits Postoperative Resynostosis in Craniosynostotic Rabbits

Abstract: These data support the initial hypothesis that interference with TGF-beta2 function inhibited postoperative resynostosis in this rabbit model. They also suggest that this biologically based therapy may be a potential surgical adjunct to retard postoperative resynostosis in infants with craniosynostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 50 publications
6
35
0
Order By: Relevance
“…Suturectomy control rabbits were somewhat smaller than IgG control individuals for most distances of the snout and face (by 3% to 4%), despite being slightly longer in a distance of the neurocranium, whereas anti-Tgf-β2 rabbits were somewhat larger than IgG control rabbits in most distances (up to 4.8%). Mooney et al (2007a) reported similar findings in that IgG control rabbits exhibited slightly slower reossification rates than did suturectomy control rabbits at 25 and 42 days of age, although the differences were not statistically significant. The authors suggested that this was probably not an effect of the IgG but rather was due to the presence of the collagen vehicle itself in the suturectomy site, which may have had an osteoinhibitory effect on reossification of the suturectomy site during degradation (Mooney et al, 2007a).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Suturectomy control rabbits were somewhat smaller than IgG control individuals for most distances of the snout and face (by 3% to 4%), despite being slightly longer in a distance of the neurocranium, whereas anti-Tgf-β2 rabbits were somewhat larger than IgG control rabbits in most distances (up to 4.8%). Mooney et al (2007a) reported similar findings in that IgG control rabbits exhibited slightly slower reossification rates than did suturectomy control rabbits at 25 and 42 days of age, although the differences were not statistically significant. The authors suggested that this was probably not an effect of the IgG but rather was due to the presence of the collagen vehicle itself in the suturectomy site, which may have had an osteoinhibitory effect on reossification of the suturectomy site during degradation (Mooney et al, 2007a).…”
Section: Discussionsupporting
confidence: 69%
“…Mooney et al (2007a) reported similar findings in that IgG control rabbits exhibited slightly slower reossification rates than did suturectomy control rabbits at 25 and 42 days of age, although the differences were not statistically significant. The authors suggested that this was probably not an effect of the IgG but rather was due to the presence of the collagen vehicle itself in the suturectomy site, which may have had an osteoinhibitory effect on reossification of the suturectomy site during degradation (Mooney et al, 2007a). A recent in vitro study (Premaraj et al, 2006) also has shown that the collagen vehicle alone had a short-term inhibitory effect on osteoblast cell number in culture.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations